1997
DOI: 10.1177/002076409704300306
|View full text |Cite
|
Sign up to set email alerts
|

Family and Cultural Correlates of Depression Among Chinese Elderly

Abstract: This study hypothesized that depressive experiences of the elderly could be aggravated by universal factors such as low social status, poor health, financial strain, and unhealthy lifestyle, as well as by factors specific to an indigenous socio-cultural environment (stressful family dynamics) of a given population. Three hundred and fifty Chinese subjects aged 65 or older were interviewed either at their homes or in the geriatric out-patient clinic of Beijing Hospital. Hierarchical logistic regression was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 35 publications
5
30
0
1
Order By: Relevance
“…Depression was more frequent in women, and an inverse relationship between education and depression prevalence was observed 42,43 . In addition, we found a higher depression prevalence in participants reporting stressful events, as has also been found in other studies 32,44,45 . Cognitive impairment was also more common among participants with depression than in persons without depression.…”
Section: Discussionsupporting
confidence: 91%
“…Depression was more frequent in women, and an inverse relationship between education and depression prevalence was observed 42,43 . In addition, we found a higher depression prevalence in participants reporting stressful events, as has also been found in other studies 32,44,45 . Cognitive impairment was also more common among participants with depression than in persons without depression.…”
Section: Discussionsupporting
confidence: 91%
“…Findings from research in mainland China and Hong Kong have revealed that elderly Chinese who had poor physical health appeared to suffer from a higher level of depression than those with good physical health status (Chou & Chi, 2002;Woo et al, 1994;Zhang et al, 1997). More specifically, Chou and Chi (2002) found that among several common chronic illnesses, arthritis is the only health problem that had a significantly unique effect on depressive symptoms.…”
Section: Journal Of Gerontological Social Workmentioning
confidence: 99%
“…More specifically, Chou and Chi (2002) found that among several common chronic illnesses, arthritis is the only health problem that had a significantly unique effect on depressive symptoms. Other studies pointed out that the aggregated level of chronic illnesses that interfere with a person's physical mobility had significant effect on depression (Zhang et al, 1997).…”
Section: Journal Of Gerontological Social Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the strong cultural emphasis on solidarity and interdependence among family and peers could also lead to the family and peer group placing too many demands on an individual, leaving them feeling compelled to fulfill obligations beyond their ability. While some studies found that a low level of perceived social support (Hwang et al 2000;Gao et al 2009) and a high level of social conflict (Ying and Han 2007;Zhang et al 1997) were associated with higher depression risk, increasing evidence has suggested that the associations were more nuanced than previously thought (Greenberger and Chen 1996;Tsai and Levenson 1997).…”
Section: Predictors Of Depression Among Chinese Americansmentioning
confidence: 96%